Silica Nanochannel Array Film Supported by ß-Cyclodextrin-Functionalized Graphene Modified Gold Film Electrode for Sensitive and Direct Electroanalysis of Acetaminophen - Zhou, Huaxu; Ding, Yao; Su, Ruobing; Lu, Dongming; Tang, Hongliang; Xi, Fengna (Frontiers in Chemistry, 2022)
Convenient and sensitive detection of active analytes in complex matrix is crucial in biological, medical, and environmental analysis. Silica nanochannel array film (SNF) equipped electrochemical sensors have shown excellent anti-fouling performance in direct analysis of complex samples. In this work, we demonstrated an electrochemical sensor with anti-fouling performance for highly sensitive detection of acetaminophen (APAP) based on SNF supported by ß-cyclodextrin-graphene (CDG) nanocomposite modified Au film electrode (AuF). Because of their rich surface hydroxyls and 2D lamellar structure, CDG on AuF can serve as the nanoadhesive for compact binding SNF, which can be grown by electrochemical assisted self-assembly method in a few seconds. Attributable to the electrocatalytic property of graphene and the synergistic enrichment from both CD and SNF nanochannels towards analyte, the SNF/CDG/AuF sensor demonstrates sensitive detection of acetaminophen ranged from 0.2 to 50 μM with an ultralow limit-of-detection of 14 nM. Taking advantage of the anti-fouling ability of SNF, the sensor is able to realize accurate and convenient analysis of APAP in commercially available paracetamol tablets.